Thoughtful Data Science : A Programmer's Toolset for Data Analysis and Artificial Intelligence with Python, Jupyter Notebook, and PixieDust /: A Programmer's Toolset for Data Analysis and Artificial Intelligence with Python, Jupyter Notebook, and PixieDust. (2018) - Taïeb, David
No abstract available